Lending to the Borrower from Hell : Debt, Taxes, and Default in the Age of Philip II - Drelichman, Mauricio; Voth, Hans-Joachim (Book collections on Project MUSE., 2014)
"Why do lenders time and again loan money to sovereign borrowers who promptly go bankrupt? When can this type of lending work? As the United States and many European nations struggle with mountains of debt, historical precedents can offer valuable insights. Lending to the Borrower from Hell looks at one famous case--the debts and defaults of Philip II of Spain. Ruling over one of the largest and most powerful empires in history, King Philip defaulted four times. Yet he never lost access to capital markets and could borrow again within a year or two of each default. Exploring the shrewd reasoning of the lenders who continued to offer money, Mauricio Drelichman and Hans-Joachim Voth analyze the lessons from this important historical example. Using detailed new evidence collected from sixteenth-century archives, Drelichman and Voth examine the incentives and returns of lenders. They provide powerful evidence that in the right situations, lenders not only survive despite defaults--they thrive. Drelichman and Voth also demonstrate that debt markets cope well, despite massive fluctuations in expenditure and revenue, when lending functions like insurance. The authors unearth unique sixteenth-century loan contracts that offered highly effective risk sharing between the king and his lenders, with payment obligations reduced in bad times. A fascinating story of finance and empire, Lending to the Borrower from Hell offers an intelligent model for keeping economies safe in times of sovereign debt crises and defaults"--